Effect of aqueous extract Lawsonia inermis leaves on Urea, Creatinine and Histological of kidneys in white male Rats exposed to oxidative stress of H2O2 - Muhammed K. Ibrahem (Tikrit Journal of Pure Science, 2023)
This study was designed to examine, the effect of Effective aqueous extract Lawsonia inermis leaves as antioxidant  on concentration of  Urea ,Criatinine and Histological of kidneys in Albino male Rats exposed to hydrogen peroxide induced oxidative stress. This study showed that 0.5%  hydrogen peroxide concentration leds to significant increase (P<0.05( in concentration of serum urea and creatinine  comparing  with control group. While the aqueous extract of Lawsonia inermis concentration (50mg/kg) led to significant decrease (P<0.05) in concentration of serum urea and creatinine compare with control group. Also the results showed no significant increase in concentration of urea and creatinine in group exposed to oxidative stress and aqueous extract of Henna comparing with control group. The histological results of the kidney treated with (0.5%) H2o2 showed degeneration, congestion, lymphatic infilteration, vacuolation in the renal tubules with necrosis comparing with control. While sections of kidney treated with aqueous extract of Henna showed normal appearance of the renal  tubules. Histological investigation of kidneys rats treated with H2O2 and extract of Henna showed improvement  in histological picture with reduction in infilteration, vacuolation and necrosis but the tissue did not return back to the normal state.